Oral administration of probiotic Escherichia coli after birth reduces frequency of allergies and repeated infections later in life (after 10 and 20 years) - Lodinová-Zádníková, Rája; Cukrowska, Bozena; Tlaskalova-Hogenova, Helena (International archives of allergy and immunology, 2003)
BACKGROUND: The development of allergies is a complex in which both composition and influence of the intestinal flora play an important role. We observed in earlier studies that the presence of an orally administered probiotic Escherichia coli strain in the intestine stimulated both a serum and local antibody response, decreased the presence of pathogens, the number of infections and the need for antibiotics. METHODS: The preventive effect of oral colonization after birth with a probiotic E. COLI strain was assessed by evaluating the results of a questionnaire both 20 years (150 full-term infants) and 10 years (77 preterm infants) after colonization. RESULTS: Differences in occurrence of allergies in colonized and control subjects were statistically significant both after 10 and 20 years (p < 0.01). Specific serum IgE antibodies confirmed the presence of allergies in 100% of 10-year-old and 91% of 20-year-old patients with clinical symptoms of allergy. Ten years after colonization, the occurrence of repeated infections was significantly lower in colonized subjects than it was in controls (p < 0.01); 20 years later, no differences were found in these groups. CONCLUSIONS: Intentional colonization of the intestine with E. coli after birth (offering the advantage of the first colonizer) was found to decrease the incidence of allergies and repeated infections in later life.
Keywords: Respiratory Tract Infections; Administration, Oral; střeva; retrospektivní studie; infekce; Respiratory Hypersensitivity; Tonsillitis; časná přecitlivělost; respirační alergie; novorozenec nedonošený; probiotika; Immunoglobulin E; Child; otitida; aplikace orální; Eczema; dítě; Adult; dospělí; infekce dýchací soustavy; Escherichia coli; incidence; průzkumy a dotazníky; Hypersensitivity, Immediate; novorozenec; tonzilitida; Infections; lidé; Humans; ekzém; imunoglobulin E; Infant, Newborn; Infant, Premature; Probiotics; Retrospective Studies; Intestines; Surveys and Questionnaires; Incidence; Otitis